O diabo na igreja: estudo de alguns discursos identitários de uma universidade confessional da região do Grande ABC - Pereira, Andréa da Silva (2007)
This research aims to investigate some identitary discourses of a confessional university in the Greater ABC Region, by means of the dialogical analysis/theory of M. Bakhtin and his Circle. The analysis corpora are constituted of two documents of the university: The Methodist University Pedagogical Project: period 2003-2007 (PP-UMESP 2003/2007) and the Director Plan: period 1993-1996 (PD 1993/1996). In Bakhtin and his Circle (1979/2003; 1929/1997; 1929/1995; 1926/1997), the dialogism principle, that allows the identification of the other in the verbal language, will serve as the main theoretical foundation. The bakhtinian notions of verbal interaction, reported discourse, of text, of discourse genre and of voices contribute even more to the study of the dialogical character of the verbal discourse. Going along with the current philosophical basis of language of the Russian Bakhtinian thought, some theoretical discursive notions of the French school, elaborated by D. Maingueneau (2004; 1998/2001/ 1987/1997) the enunciative shift, the deictic elements of person, space and time, the designation types and the enunciative vocation and by J. Authier-Revuz (1998) it is hereby highlighted the study of the autonimical modalizations are also mobilized to form the theoretical construct and the analytical tools of our research corpora. The concepts of argumentative operators and of deontic modals, such as those of Koch (1992; 1987), will be used by us from the dialogical perspective of the discourse for the examination of the data. The gathering and the study of the documents extraverbal context call our attention to the presence of three discourses: the ones of the market, the pedagogy and the religion. The examination of the data on the linguistic and enunciative levels gives room to the concrete exotopy, which, on its turn, helps us, as authors of this study, to come to interpretations in two directions: The first one agrees, partly, with the position that some Sociology theoreticians adopt, which leads them to understand that the Brazilian confessional universities discourse as a marketing strategy. The second one considers the socio-historical aspects that appear in both of the analyzed documents and that characterize the religious discourse in as far as it is peculiar to the Methodist tradition. The final results point to an important presence of the market oriented discourse as the other that builds the identity of the Confessional University hereby, object of this investigation. This project, in what it allows us to study language as work, finds its place in the research line Language and Work, of the Program of Applied Linguistics and Language Studies (LAEL - Programa de Lingüística Aplicada e Estudos da Linguagem), of the PUC/SP (Pontific Catholic University/São Paulo)